A Comparison of Marijuana Use Across Different Levels of Justice-Involved Populations - Martins, Traccy A.W. (Journal of drug issues, 2022)
A large portion of the U.S. population is justice-involved, an important at-risk population with poor physical/mental health outcomes and increased rates of substance use. Using the 2018 National Survey on Drug Use and Health, the current study assesses marijuana use across level of community-based justice involvement (i.e., arrest, probation, and parole) among adults. Given increasing rates of marijuana use and a relative lack of research, the current study addresses an important gap in the literature. Findings from logistic regression analysis show that adults who had been arrested or were on probation were more likely to use marijuana compared to adults with no justice involvement, while adults on parole were less likely to use marijuana than those on probation. This study offers evidence of differences in marijuana use across level of justice involvement, which may be attributable to other substance use behaviors, and has important implications for criminal justice practice.